Dimeters in $L_2$ classes of differentiated functions determined by continuity moduli of higher orders - Shalaev , V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
Sharp inequalities are obtained in the space $L_2$, connecting the best approximations of differentiable $2π$-periodic functions by trigonometric polynomials with integrals containing the higher-order moduli of continuity of the derivatives of these functions. The Kolmogorov widths of certain classes of functions, defined by these moduli of continuity, are computed.